Analysis of Factors Affecting Capital Structure in Food and Beverage Manufacturing Company - Nur Hajja Aini; St Habibah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2018)
The purpose of this research to analyze the influence of firm size, liquidity, growth opportunities, tangibility asset, and business risk to the capital structure of listed food and beverage manufacturing companies in Indonesia and Vietnam Stock Exchange from 2010 to 2016. The result shows that the fixed effects model should be appropriate for this study as compared to the random effect model. Capital structure significantly differences between the two countries. Firm size has a positive but insignificant influence on the capital structure in Indonesia, whereas it has a positive and a significant influence on the capital structure in Vietnam. Liquidity has a negative and significant influence on the capital structure both in Indonesia and Vietnam. Growth opportunities have a negative but insignificant influence on the capital structure both in Indonesia and Vietnam. Asset tangibility has a positive but insignificant influence on the capital structure in Indonesia, but it has the negative but insignificant influence on the capital structure in Vietnam. Ultimately, the business risk has a negative and significant influence on the capital structure in Indonesia but has a positive and insignificant influence on the capital structure in Vietnam.